2023
DOI: 10.1002/anse.202300031
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Three‐Component Petasis Reactions Accelerated in Microdroplets: Reaction Optimization and Senstive Detection by Mass Spectrometry

Abstract: Due to their important roles in medicine, the product of the Petasis reaction has attracted extensive interest in pharmaceutical, medical and chemical communities. Traditional three‐component Petasis methods normally use various catalysts under harsh conditions (high temperature, microwave, etc.) for long reaction times. In this study, we developed a green and highly efficient microdroplet method for accelerating the Petasis reaction, which obtain good yields without the need of any catalysts under mild reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Our previous studies demonstrated a moderate correlation of Betti and Petasis reactions in microdroplets to reaction temperature (controlled by the heated chamber through which microdroplets flew) and collection temperature (controlled by placing the collection flask in a water/ice bath). The temperature effect of the Passerini microdroplet reaction was hence investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies demonstrated a moderate correlation of Betti and Petasis reactions in microdroplets to reaction temperature (controlled by the heated chamber through which microdroplets flew) and collection temperature (controlled by placing the collection flask in a water/ice bath). The temperature effect of the Passerini microdroplet reaction was hence investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, three-component Biginelli, Hantzsch, Mannich, , Betti, Povarov, and Petasis reactions and a five-component spiro-pyrrolidine construction have been unlocked by microdroplet chemistry, where the three-component Passerini reaction has not yet been uncovered. Additionally, the above MCR examples were limited to milligram-scale synthesis except the Betti reaction and Petasis reaction, restricting the applicability of microdroplet chemistry in MCRs. A gram-scale microdroplet Passerini methodology is highly desirable to the construction of α-acyloxy carboxamides considering their bioactive importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, organic applications of microdroplet chemistry were classified into five major classes including addition/elimination (Schiff base reactions, Katritzky transamination, Claisen–Schmidt condensation, Michael addition, etc. ), oxidation/reduction, ,,,,, biphasic reactions (gas–liquid, ,,, liquid–liquid, and liquid–solid , reactions), multicomponent reactions (Hantzsch, Biginelli, Betti, Petasis and Passerini reaction, N-alkylation, five-component spiro-pyrrolidine construction, etc. ), and others (Pinacol and Beckmann rearrangement, metal catalysis, etc.).…”
Section: Introductionmentioning
confidence: 99%